Leveduras patogênicas em fezes de aves de cativeiro: relação fenotípica e genotípica entre os isolados - Reis, Eduardo José de Carvalho [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Men and animals have an age-old relationship, where the group of birds, in particular, is widely used for various purposes, such as food and company.Men and animals have an age-old relationship, where the group of birds in particular is widely used for various purposes, such as food and company. The birds are portrayed as disseminators of pathogens to the environment, however, knowledge about this role certain avian species, closely correlated to humans, are somewhat scarce. This study aimed to isolate, identify and characterize the phenotype and the genotype obtained yeast stool five captive birds: chicken (Gallus gallus domesticus), Love bird (Agapornis spp), Budgerigar (Melopsittacus undulatus) cockatiel (Nymphicus hollandicus) and canary (Serinus canaria domesticus). Therefore, we evaluated 247 stool samples of these five avian species from seven cities located in the northwest from State of São Paulo, southern of Minas Gerais and southwestern Mato Grosso do Sul. The collection was performed using sterile spatulas. The material was seeded in Sabouraud dextrose agar and seed Niger agar, with titrations. The identification of species was based on biochemical and macro and micromorphological characteristics. In addition, all isolates identified were submitted to antifungal susceptibility testing by disk diffusion (CLSI, M44-A), compared to amphotericin B, ketoconazole, fluaconazole and itraconazole. The occurrence of yeasts occurred in 89% of samples, ranging from 77.5% to 94.0% of the studied independently bird. There were obtained 318 isolates belonging to 29 different species. There were obtained 318 isolates belonging to 29 different species. The prevalent genus isolated was Candida with 183 (57.5%), followed by Cryptococcus with 45 (14.2%), Rhodotorula with 38 (11.9%) and Trichosporon with 36 (11.3%); other genres totaled 16 isolates (5.0%). Note that, in the number of fungal species isolated, C. albicans, C. guilliermondii, C. ...

Os homens e animais possuem uma relação milenar, em que o grupo das aves, em especial, é utilizado amplamente para diversas finalidades, tais como alimentação e companhia. As aves são retratadas como disseminadoras de patógenos ao ambiente, entretanto, o conhecimento a respeito deste papel a determinadas espécies aviárias, intimamente correlacionadas ao ser humano, são um tanto escassos. O presente trabalho teve como objetivos isolar, identificar e caracterizar o fenótipo e o genótipo de leveduras obtidas de fezes de cinco aves de cativeiro: galinha (Gallus gallus domesticus), Pássaro-do-amor (Agapornis spp), Periquito-australiano (Melopsittacus undulatus) calopsita (Nymphicus hollandicus) e canário (Serinus canaria domesticus). Para tanto, foram avaliadas 247 amostras de fezes destas cinco espécies aviárias, provenientes de sete cidades localizadas na região noroeste do estado de São Paulo, Sul de Minas Gerais e sudoeste do Mato Grosso do Sul. A coleta foi realizada com auxílio de espátulas estéreis. O material foi semeado em ágar Sabouraud dextrose e ágar semente de Níger, como titulações. A identificação das espécies baseou-se nas características macro e micromorfólogicas, e bioquímicas. Ademais, todos os isolados identificados, foram submetidos ao teste de antifungigrama por disco-difusão (CLSI, documento M44-A), frente a anfotericina B, cetoconazol, fluconazol e itraconazol. Aqueles que apresentavam padrões de suscetibilidade dose-dependente ou resistente, foram submetidos ao teste de microdiluição em caldo (CLSI, documento M27-A3). A ocorrência de leveduras se deu em 89% das amostras, variando de 77,5% a 94,0% independente da ave estudada. Foram obtidos 318 isolados, pertencentes a 29 espécies diferentes. O gênero prevalente foi Candida com 183 isolados (57,5%), seguido de Cryptococcus com 45 (14,2%), Rhodotorula com 38 (11,9%) e Trichosporon com 36 (11,3%); os demais gêneros totalizaram 16 isolados...
Keywords: Microbiologia; Fungos patogenicos; Ave domestica - Esterco; Atividade antifúngica; Levedos; Pathogenic fungi